2018
DOI: 10.3389/fphar.2018.01190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture on the Quality of Life in Patients With Migraine: A Systematic Review and Meta-Analysis

Abstract: Background: Acupuncture is frequently used as an efficient method to prevent and treat migraines. However, its effect on the quality of life remains controversial.Methods: Seven databases, such as PubMed and Cochrane Library were searched to retrieve reference lists of eligible trials and related reviews. Randomized controlled trials that were published in Chinese and English were included.Results: Acupuncture resulted in lower Visual Analog Scale scores than the medication group at 1 month after treatment (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
0
14
0
2
Order By: Relevance
“…Patients were followed for 24 weeks in total At 16 weeks, the frequency of migraine attacks decreased the most with acupuncture (mean [SD] 3.2 [2.1]) compared with sham acupuncture (2.1 [2.5]) or with no treatment (1.4 [2.5]). The acupuncture group also had the significantly lowest frequency of migraine attacks, migraine days, and VAS scores at each follow-up time-point between weeks 4 and 24 True acupuncture might be more efficacious in the long-term treatment of migraines without aura compared with sham acupuncture or being on a waiting list Jiang et al (2018) [ 54 ] 62 RCTs involving 4947 total patients diagnosed with migraines (± aura) Patients either received no treatment, sham acupuncture, medication, or treatment acupuncture The acupuncture group had lower VAS scores than the medication group at 1 month post-treatment (mean difference 1.22, 95% CI − 1.57 to − 0.87) and at 1–3 months post-treatment (− 1.81, 95% CI − 3.42 to − 0.20). The acupuncture group also had lower scores at 1 month post-treatment than sham acupuncture (− 1.56, 95% CI − 2.21 to − 0.92).…”
Section: Evidence For Acupuncturementioning
confidence: 99%
See 1 more Smart Citation
“…Patients were followed for 24 weeks in total At 16 weeks, the frequency of migraine attacks decreased the most with acupuncture (mean [SD] 3.2 [2.1]) compared with sham acupuncture (2.1 [2.5]) or with no treatment (1.4 [2.5]). The acupuncture group also had the significantly lowest frequency of migraine attacks, migraine days, and VAS scores at each follow-up time-point between weeks 4 and 24 True acupuncture might be more efficacious in the long-term treatment of migraines without aura compared with sham acupuncture or being on a waiting list Jiang et al (2018) [ 54 ] 62 RCTs involving 4947 total patients diagnosed with migraines (± aura) Patients either received no treatment, sham acupuncture, medication, or treatment acupuncture The acupuncture group had lower VAS scores than the medication group at 1 month post-treatment (mean difference 1.22, 95% CI − 1.57 to − 0.87) and at 1–3 months post-treatment (− 1.81, 95% CI − 3.42 to − 0.20). The acupuncture group also had lower scores at 1 month post-treatment than sham acupuncture (− 1.56, 95% CI − 2.21 to − 0.92).…”
Section: Evidence For Acupuncturementioning
confidence: 99%
“…Furthermore, the analysis showed that acupuncture had a lower risk than medication of causing adverse events (risk difference − 0.16, 95% CI − 0.25 to − 0.06). The authors concluded that acupuncture is more effective than no treatment, sham treatment, or medication in treating and preventing migraines and that it is also associated with a greater enhancement in quality of life compared to medication [ 54 ].…”
Section: Evidence For Acupuncturementioning
confidence: 99%
“…Иглорефлексотерапия рекомендуется в качестве профилактического лечения мигрени, эффективна при ее эпизодической и хронической форме [109][110][111].…”
Section: немедикаментозное лечениеunclassified
“…Acupuncture has been shown to be effective in the treatment of chronic pain conditions 912 including shoulder pain, 13 chronic low back pain, 1416 neck pain, 14,17 knee pain from OA, 18,19 headache 20,21 and temporomandibular disorders. 22 Moreover, an individual patient meta-analysis of 39 trials (20,837 patients) found clear evidence that the effects of acupuncture persist over time with only a small decrease (15%) in treatment effect at 1 year.…”
Section: Introductionmentioning
confidence: 99%